TRAINING ON CARING FOR THE CORPSE For Mts Nurul Jadid Paiton Probolinggo’s Students - Muhammad Iqbal Dewantara; M Mahbubi; Suryanto Suryanto; Mahbub Junaidi (BAMALA Institute, 2024)
The sad condition of families in the area is that they often experience the inability to take care of the corpse. Caring for the Corpse becomes fardhu kifayah for Muslims in organizing the management of the Corpse with the obligation to bathe, shroud, pray and bury, because the series of corpse management processions are meaningful in the value of community life. The above problems are the reason for us, the to form a community service team (PKM) and conduct training on funeral arrangements as an effort to help knowledge in the management of the corpse. This PKM uses lecture and practice methods, namely by providing theoretical and practical science material. The hope is that all people, especially students, can know and master the funeral arrangements so that the mutual obligation or fardhu kifayah can be carried out properly. The training activities are intended to socialize the role and function and cadre of amil jenazah in the implementation of funeral arrangements. It is hoped that this training can maximize the role of humanist and religious values for the benefit of the community.